Individualization as one of the directions of optimization training process of hockey players at the age of 14-16 years old - Kugayevskiy S.A (Kharkov National Pedagogical University, 2012)
Material about the level of development of training process in hockey is resulted. Directions of construction of training process of hockey players, applications of different facilities and methods of preparation are considered. Opinions of specialists in this type of sport are studied. The ways of optimization of training process are resulted. It is expounded information about the changes of indexes of D&K-test of testing of hockey players at the individual construction of seasonal preparation and in transition on the command training program. Loadings given about different influence are confirmed with one orientation on the sportsmen of different biotpower groups of D&K-test.